The Peculiarities of Investment Policy in Tourism Sector - Khachatryan, Nonna (Bulletin of Yerevan University G: Economics, 2014)
The article discusses different theoretical approaches of investment effectiveness assessments in tourism industry and, according to these, suggests multifarious advance analyses of investing resources returns. In particular, it is preferred to use the multi-faceted approach analysis of the effectiveness of investments in terms of business travel companies and motivations of the state, taking into account socio-economic and environmental factors.
Keywords: attractivness of investments, tourism product, service of tourism, return of investments